2015
DOI: 10.7567/jjap.55.02bf02
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled oleamide layer applied for cathode buffer layer of bulk heterojunction solar cells based on PTB7:PC71BM

Abstract: In this work, bulk heterojunction solar cells based on poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]-thiophenediyl]] and phenyl-C71-butyric-acid-methyl-ester were fabricated using 1,2-dichlolobenzene solutions containing different weight ratios of oleamide. The oleamide layers were self-assembled on the active layer surfaces during the solidification of the active layer after spin coating. A significant increase in open-circuit voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Two different studies reported the segregation of oleamide, an amphiphilic surfactant, to the BHJ surface during spin coating and corresponding improved device PCE, as shown in Figure and Table . , Furthermore, surface Kelvin Probe measurements indicated that the surface ionization potential of films with oleamide was higher than that of P3HT:PCBM or PTB7:PC 71 BM blends with no additive. The higher ionization potential is associated with a work function reduction of the adjacent Al cathode and improved electron collection.…”
Section: Interlayer Formation Due To Additive Density Amphiphilic Cha...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two different studies reported the segregation of oleamide, an amphiphilic surfactant, to the BHJ surface during spin coating and corresponding improved device PCE, as shown in Figure and Table . , Furthermore, surface Kelvin Probe measurements indicated that the surface ionization potential of films with oleamide was higher than that of P3HT:PCBM or PTB7:PC 71 BM blends with no additive. The higher ionization potential is associated with a work function reduction of the adjacent Al cathode and improved electron collection.…”
Section: Interlayer Formation Due To Additive Density Amphiphilic Cha...mentioning
confidence: 99%
“…Solar cell structure with oleamide interlayer (inset), and current density–voltage ( J – V ) curves of PTB7:PC71BM BHJ with oleamide. Reproduced with permission from ref . Copyright 2016 The Japan Society of Applied Physics.…”
Section: Interlayer Formation Due To Additive Density Amphiphilic Cha...mentioning
confidence: 99%